2021
DOI: 10.21273/horttech04779-20
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro–Ex Vitro Micropropagation System for Hemp

Abstract: Hyperhydricity of shoots initiated in vitro, poor shoot extension, inability of shoot cultures to maintain good growth over an extended time, and unsuccessful ex vitro rooting have limited the development of a commercial scale micropropagation system for hemp (Cannabis sativa). We present a culture initiation method that prevents shoot hyperhydricity using vented-lid vessels with 0.2-µm pores and medium containing agar at 1% (w/v). To optimize shoot multiplication in vitro, a control medium (medium A) and four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…Meristems have not been previously tested as an explant source in either hemp or cannabis, although shoot tips were used for direct regeneration of hemp (Wang et al, 2009 ), and stem tips were used for micropropagation and retipping studies on hemp (Lubell-Brand et al, 2021 ). Meristems are important starting material, as they contain a lower frequency of internally-borne microbes and viruses (Wang and Hu, 1980 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Meristems have not been previously tested as an explant source in either hemp or cannabis, although shoot tips were used for direct regeneration of hemp (Wang et al, 2009 ), and stem tips were used for micropropagation and retipping studies on hemp (Lubell-Brand et al, 2021 ). Meristems are important starting material, as they contain a lower frequency of internally-borne microbes and viruses (Wang and Hu, 1980 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al ( 2009 ) used an MS basal salts medium with 30 g/L sucrose, 6.8 g/L phytagel, and 1 μM of TDZ to produce axillary buds from shoot tips of hemp during micropropagation. Lubell-Brand et al ( 2021 ) used an MS salts medium described by Lata et al ( 2016 ) in which TDZ was replaced with the growth regulator meta-topolin (mT). They reported that hyperhydricity was reduced by modifying the agar content of the medium, coupled with improved vessel ventilation and enhanced nitrogen levels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations